A guide to the published works of Benjamin Constant - Courtney, C (Voltaire Foundation, 2017)
Introduction Acknowledgements Abbreviations Summary of checklist Checklist of the published works of Benjamin Constant A Separate works B Speeches and official papers C Contributions to collective works and works by other writers D Contributions to periodicals and newspapers E Collections and selections F Correspondence G The Acte additionnel aux constitutions de l'Empire, 1815 Chronology of the works of Benjamin Constant Appendices 1. Classified list of translations 2. Bibliographical writings on Benjamin Constant: a select list Indexes Chronological index of editions General index